Sarcopenia is a predictor of outcomes after lobectomy - Miller, James A.; Harris, Kassem; Roche, Charles; Dhillon, Samjot; Battoo, Athar; Demmy, Todd; Nwogu, Chukwumere E.; Dexter, Elisabeth U.; Hennon, Mark; Picone, Anthony; Attwood, Kristopher; Yendamuri, Sai (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
Background: As screening for lung cancer rises, an increase in the diagnosis of early stage lung cancers is expected. Lobectomy remains the standard treatment, but there are alternatives, consideration of which requires an estimation of the risk of surgery. Sarcopenia, irrespective of body mass index, confers a worse prognosis in many groups of patients including those undergoing surgery. Here we examine the association of muscle mass with outcomes for patients undergoing lobectomy. Methods: Consecutive patients undergoing lobectomy were retrospectively reviewed. Preoperative computed tomography scans were reviewed, and cross-sectional area of the erector spinae muscles and pectoralis muscles was determined and normalized for height. Univariate and multivariate analyses were then done to examine for an association of muscle mass with morbidity and short- and long-term mortality. Results: During the study period, there were 299 lobectomies, 278 of which were done by video assisted thoracoscopic surgery. The average age of the patients was 67.5±10.6 years. Overall complication rate was 52.2%, pneumonia rate was 8.7%, and the 30-day mortality rate was 1.3%. Mean height adjusted-erector spinae muscle cross-sectional area was 10.6±2.6 cm2/m2, and mean height adjusted-pectoralis muscle cross sectional area was 13.3±3.8 cm2/m2. The height adjusted cross sectional areas of the erector spinae and pectoralis muscles were not associated with overall complication rate, rate of pneumonia, readmission, or intensive care unit length of stay. The height adjusted-erector spinae muscle cross sectional area was inversely correlated with 30-day mortality risk, odds ratio 0.77 (95% CI, 0.60–0.98, P=0.036). Mean length of stay was 7.0 days (95% CI, 5.5–8.4 days). Multivariate analysis demonstrated a significant inverse association of the height adjusted-erector spinae muscle cross sectional area with length of stay (P=0.019). Conclusions: The height adjusted-erector spinae muscle cross sectional area was significantly associated with 30-day mortality and length of stay in the hospital. Measurement of muscle mass on preoperative computed tomography imaging may have a role to help predict risk of morbidity and mortality prior to lobectomy.